The Role of Islamic Religious Education in Strengthening Adolescent Mental Health: Study of Qur’an Surah Yunus (10:57) - Adisty Ningtiyas; Abdur Razzaq; Kristina Imron (MAN 4 Kota Pekanbaru, 2025)
The concept of mental health in adolescents is crucial to understand, particularly from an Islamic perspective. Adolescents are vulnerable to identity crises; therefore, Islamic views on mental health can serve as a foundation for shaping their thoughts and behavior. This study aims to raise awareness among adolescents regarding how to maintain mental well-being and understand the developmental changes they experience, by exploring patterns of Islamic education grounded in the Qur’an and Sunnah. This research employs a library research approach, with data collected from journals, books, newspapers, online sources, and other relevant references. The findings indicate that, from an Islamic perspective, mentally healthy adolescents are those who are able to practice worship in accordance with Islamic teachings, face various life challenges, adapt to new situations, build positive relationships with their surroundings, and strengthen their relationship with God.